The Gene-Lifestyle Interaction on Leptin Sensitivity and Lipid Metabolism in Adults: A Population Based Study - Luglio, Harry Freitag; Sulistyoningrum, Dian Caturini; M.Kes, Emy Huriyati; Yi, Yi Lee; Wan Muda, Wan Abdul Manan (MDPI, 2017)
Background: Obesity has been associated with leptin resistance and this might be caused by genetic factors. The aim of this study was to investigate the gene-lifestyle interaction between